The geoelectric field coast effect: Results from two dimensional finite element method and analytic solutions - Xuan Wang; Shuming Zhang (Alexandria Engineering Journal, 2023)
The geoelectric fields induced during geomagnetic disturbances (GMD) may affect the normal operation of technological systems at the Earth’s surface. The non-uniform Earth conductivity structure, especially large lateral conductivity contrasts, can lead to the enhancement of geoelectric fields near boundaries such as a coastline. In this paper, we give an overview of the applicability of a two-dimensional finite element method (2D-FEM) for studying lateral variations of the Earth’s conductivity, which can be considered as one of magnetotelluric sounding forward modelling methods, including both the E and the H polarization cases. Then the spatial distribution of the geoelectric field near a continent-ocean boundary is calculated with different models. This is compared with analytic solutions for simple models to verify the accuracy of the FEM modelling, which is calculated by using the ANSOFT software. More realistic scenarios are then developed to emphasize the advantages of FEM. The factors influencing the coast effect are discussed. Results show that frequency, the shape of seafloor boundaries, and the depth of ocean have a significant impact on the geoelectric fields. Therefore, these factors should attract more attention when assessing risk for man-made conducting systems located within the coastal influence range.